The GDP impact on international tourism demand : a Slovenia based case - Nemec Rudež, Helena (2008)
Abstract: The paper empirically examines the relationship between Slovenian GDP and international tourism expenditures of Slovenia in the period 1994-2006. For this purpose, regression analysis in different functional forms was used to examine the impact of GDP on international tourism expenditures. The results reveal positive and strong impact of GDP on international tourism expenditure in Slovenia in the given period of time. Further, income elasticity of outbound tourism demand was calculated leading to the conclusion that travelling in foreign destinations has characteristics of a luxury good for Slovenian people
Bibliografija: 27 jed
Keywords: Turizam -- Slovenija